A Study On Consumer Behaviour Of The Young Decision- Makers Of India (Trinity Journal of Management, IT & Media (TJMITM), 2013)
All of us are consumers and we consume things of daily  use which we consume and buy according to our needs,  preferences and buying power. Consumer behaviour can  be defined as the decision-making process and physical  activity involved in acquiring, evaluating, using and  disposing of goods and services. Consumer companies  thus realizing that the Indian consumer market is a tough  nut to crack but the one they can't do without. Consumer  behavior is the study of when, why, how, and where  people do or do not buy a product. It blends elements from  psychology, sociology, social anthropology and economics. The emerging market is used to evaluate the  socio economic scenario of the country in terms of the  growth of the market and industrial development. The  Indian consumer market has never had it better. Higher  disposable incomes, the development of modern urban  lifestyles and an increase in consumer awareness have  affected buyer behaviour — in cities, towns and even rural  areas. On the other hand we said that the main factors  behind this booming emerging market are the economic  liberalization and the perfect competition market, the high  standard of living and per capita income, the development  of medical facilities and infrastructure, the increase in  foreign investments etc. Due to the favourable emerging  market, more and more industries are being set up and the  customer base is also increasing. Currently, India is the 4th  largest economic system in the world in terms of the  purchasing power parity. The recent economic development has also put a positive impact on the various  sectors. There are too many question floating in the air, the  major ones are what the reasons of changes in Consumer  Buying Behaviour are? How the Indian Consumer Market  change from pyramid to sparkling diamond? What type of  Emerging Market the companies dealing with? This  primary data based research paper is an attempt to answer  the above major questions and present the linkage  between consumer preferences and the impact of change  in the buying patterns of the consumers. The starting point  of the study is to analyse the changing conditions of the  products in Indian Market and this study will also be useful  to bridge the gap between theory and practice and will  provide valuable insight to the managers involved in  Marketing and Selling of products and services in Indian  Market.
Keywords: Indian Consumer Market; Economic Liberalization; Emerging Market